2017
DOI: 10.1021/acschemneuro.7b00094
|View full text |Cite
|
Sign up to set email alerts
|

The Isomeric Preference of an Atypical Dopamine Transporter Inhibitor Contributes to Its Selection of the Transporter Conformation

Abstract: Cocaine, a widely abused psychostimulant, inhibits the dopamine transporter (DAT) by trapping the protein in an outward-open conformation, whereas atypical DAT inhibitors such as benztropine have low abuse liability and prefer less outward-open conformations. Here, we use a spectrum of computational modeling and simulation approaches to obtain the underlying molecular mechanism in atomistic detail. Interestingly, our quantum mechanical calculations and molecular dynamics (MD) simulations suggest that a benztro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 102 publications
2
68
0
2
Order By: Relevance
“…For a range of numbers of MIs (50, 75, 100, 150, 200, 300), we estimated an MSM for each situation and concluded that the 100-MI MSM performs best based on two analysis. We first calculated scores in terms of variational principle [ 44 , 45 ], using cross-validation [ 46 ] as previously described [ 47 ]. This analysis showed the variational scores were comparable for small numbers of MI and decreased when the number of MI is larger than 150.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a range of numbers of MIs (50, 75, 100, 150, 200, 300), we estimated an MSM for each situation and concluded that the 100-MI MSM performs best based on two analysis. We first calculated scores in terms of variational principle [ 44 , 45 ], using cross-validation [ 46 ] as previously described [ 47 ]. This analysis showed the variational scores were comparable for small numbers of MI and decreased when the number of MI is larger than 150.…”
Section: Methodsmentioning
confidence: 99%
“…e ., if Eq ( 1 ) can be satisfied: where P (τ) is the transition matrix estimated from the data at lag time τ (the Markov model), and P ( k τ) is the transition matrix estimated from the same data at longer lag times k τ. In practice, we use P ( k τ) and P k (τ), respectively, to propagate probability starting from one of the metastable states, and measure how much probability ends up in each metastable state [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…S3D). These changes are characteristic features of the transporter transitioning to an inward-facing conformation [39][40][41].…”
Section: Jjc8-091 Reduces and Jjc8-088 Enhances Optical Brain-stimulamentioning
confidence: 99%
“…To further characterize this observation, we quantified differences of structural elements between the hDAT/JJC8-091 and hDAT/JJC8-088 complexes, by applying the previously described pairwise interaction analyzer for DAT (PIA-DAT) [39]. Specifically, our analysis showed that the side chain phenyl group of Phe320 rotates to a "closed" conformation in the presence of JJC8-091, but not JJC8-088, making hydrophobic interactions with the propanol moiety of JJC8-091 ( Fig.…”
Section: Jjc8-091 Reduces and Jjc8-088 Enhances Optical Brain-stimulamentioning
confidence: 99%
“…In previous studies of specific biomolecular systems with MSMs based on MD simulations, reported longest implicit timescales turned out to be smaller than the aggregate sampling by at least one order of magnitude [5][6][7][8][9][10][11][12][13][14][15][16][17] or comparable to the aggregate sampling. [18][19][20][21][22] In this paper, we analyze several MSMs with different topologies to uncover the reasons for the above empirical rule. These MSMs represent typical cases when slow dynamics is observed in biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%